Forage potential of S3 corn progenies in topcrosses and selection of testers of different genetic bases - Rosa, Jocimar Costa; Faria, Marcos Ventura; Zaluski, Welton Luiz; Gava, Emanuel; Andreoli, Pedro Henrique Willemann; Sagae, Vitor Seiti (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to identify corn (Zea mays) genotypes with forage potential and to evaluate the efficiency of testers to discriminate forage traits in topcrosses, considering the contribution of additive and nonadditive genes. The experiment was carried out in the 2015/2016 and 2016/2017 crop seasons, in a randomized complete block design with three replicates. Thirty S3 corn progenies were evaluated in topcrosses with the AG8025, P30B39, MLP102, 60.H23.1, and 70.H26.1 testers. The following traits were assessed: forage dry mass yield, neutral detergent fiber, acid detergent fiber, and forage dry mass degradability. Progenies 205.2, 159.6, and 199.2, in this order, presented the best performance for forage potential. Testers 60.H23.1 and 70.H26.1 better expressed the genetic variability between progenies. For all traits in both crop seasons, there is a predominance of the action of genes of nonadditive effects.